Шляхи удосконалення адміністративного законодавства у сфері здійснення нагляду та контролю за охороною, захистом, використанням та відтворенням лісів в Україні - Колісніченко, С. Ю.; Kolisnichenko, S. Yu. (Наше право. - 2021. - № 4. - С. 227-232, 2021)
У статті, спираючись на аналіз наукових поглядів вчених та норм концептуальних та стратегічних документів, опрацьовано перспективні напрямки покращення адміністративного законодавства у сфері здійснення нагляду та контролю за охороною, захистом, використанням та відтворенням лісів в Україні. Доведено, що запровадження запропонованих у статті змін дозволить якісно покращити контрольно-наглядову діяльність у відповідній сфері.

It is emphasized the need to introduce regulatory and legal principles for the implementation of effective interaction of subjects of control and supervision in the field of forestry. It was noted that interaction is an extremely important factor for the existence and proper functioning of the system, in particular, the system of subjects of supervision and control over the protection, protection, use and disposal of forests, especially in conditions where the powers and tasks of the subjects are quite closely related and , even, in a number of issues overlap. It is emphasized that the establishment of deep, systematic and systematic cooperation allows control subjects to: ensure a more balanced and effective approach to checking and assessing the condition of forests, compliance with their legal regime; to avoid unnecessary spending of resources; react more promptly and effectively to offenses and other problematic points in the field of forestry It has been proven that the improvement of legal mechanisms of public participation in the system of supervision and control over the protection, protection, use and reproduction of forests in Ukraine requires the following: first, to determine the order of systematic information about the state of forests in Ukraine, about the forms and methods of forest control, measures control and supervision and their results; secondly, to introduce the procedure for involving representatives of the public in conducting control and supervision measures; etc.

В статье, опираясь на анализ научных взглядов ученых и норм концептуальных и стратегических документов, разработаны перспективные направления улучшения административного законодательства в сфере осуществления надзора и контроля за охраной, защитой, использованием и воспроизводством лесов в Украине. Доказано, что введение предложенных в статье изменений позволит качественно улучшить контрольно-надзорную деятельность в этой сфере.
Keywords: нагляд; контроль; адміністративне законодавство; охорона лісів; захист; supervision; control; administrative legislation; protection of forests; надзор; административное законодательство; охрана лесов; защита